Whitman Calculus - Guichard, David; Open Textbook Library (Open Textbook Library, 2010)
An introductory level single variable calculus book, covering standard topics in differential and integral calculus, and infinite series. Late transcendentals and multivariable versions are also available. This textbook has been used in classes at:Boise State University,Claremont McKenna College,University of Minnesota, University of Puget Sound, Western Connecticut State University, Whitman College.
1 Analytic Geometry -- 2 The Derivative -- 3 Rules for Finding Derivatives -- 4 Transcendental Functions -- 5 Curve Sketching -- 6 Applications of the Derivative -- 7 Integration -- 8 Techniques of Integration -- 9 Applications of Integration -- 10 Polar Coordinates, Parametric Equations -- 11 Sequences and Series
In English.
Description based on print resource
Keywords: Mathematics -- Textbooks